NEST ARCHITECTURE AND NESTING BIOLOGY OF VESPA TROPICA (LINNAEUS, 1758) IN BANGALORE, INDIA - PANNURE, ARATI; MUTTHURAJU, G.P.; IMARAN, SYED; BOMMESHA, B.; BHOGEESH, B.M.; PRASHANTHA, C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
This study examined the nest architecture and nesting biology of the social wasp Vespa tropica (Hymenoptera : Vespidae) in GKVK campus, University of Agricultural Sciences, Bangalore. Information on the biology and nesting habits of most of the Indian wasp's species is almost lacking. These wasps built 56 cm height nest, which is attached to the substratum by a single petiole. The immature nests were observed from June to August, 2012. Nest was completely covered with 4-7 layers of wooden fragment mixed with saliva/carton with a five combs in it. A total of 2521 cells were present with 8.34±0.17mm of cell size. The colonies had 340 females and one queen with no drones in the nest.